Determination of Seawater Intrusion Zones Using the Resistivity Method in Kelurahan Soreang, Maros District, South Sulawesi Province: Penentuan Zona Intrusi Air Laut Menggunakan Metode Tahanan Jenis di Kelurahan Soreang, Kabupaten Maros - Syamsuddin Syamsuddin; Muhammad Fajar; Andry Harmaji Wirawan; Nurul Salsabila; Rezky Rezky; Muhammad Fawzy Ismullah Massinai; Selfiana Selfiana; Bambang Harimei (JURNAL GEOCELEBES, 2023)
The seawater intrusion into the groundwater layer is one of the factors that can disrupt groundwater quality in Soreang Village, Maros Regency. This is a serious problem for the community in the area, so it is necessary to identify the seawater intrusion zone. Previous study using the resistivity method is in regional scale. In this study, two intersecting lines with a length of 470 meters each were acquired using the Wenner-Schlumberger array with a spacing of 10 meters to get local scale. Based on the resistivity value of the study area, there are three layers interpreted as a layer of fill (1 - 1000 Ωm), alluvium layer (1 - 6 Ωm) and limestone layer (≥ 7 Ωm). The seawater intrusion zone in the study area is in the alluvium layer with varying depths up to 40 meters subsurface. The results of this study can be a reference for the community or government in the search for fresh water.